The handbook of credit portfolio management (McGraw-Hill, 2009)
The Handbook of Credit Portfolio Management delivers a comprehensive and global perspective on the latest strategies for credit portfolio rebalancing and management, particularly in relation to pricing, hedging, and measuring and managing risk. Renowned author and editor Greg Gregoriou, with a team of international contributors, provides proven techniques for challenges including risk weighted asset calculation, the reevaluation of hedging strategies, and implementation of the mandatory Basel II. They explain in great detail such key topics as the evaluation of structured credit derivatives, the investment opportunities of hedge funds, basis arbitrage trading strategies, and the securitization of subprime mortgage loans from a legal perspective.